Geopolymer for medical application: a review - Puspasari, Vinda; Harmaji, Andrie; Febrina, Eva; Alverina, Clara; Siswayanti, Bintoro (Physics and Chemistry of Solid State, 2024)
The materials for medical application are normally consisted of metal, ceramic, and polymer. Each material has its own limitations such as corrosion in metal, the brittleness of ceramic, and the high temperature problem of polymer. To eliminate their weakness, combining one or more respective materials are encouraged, which termed as composite. One of the emerging composite materials that can be utilized in medical application are geopolymer, which is an inorganic polymer material consisted of aluminosilicate sources such as metakaolin and sol-gel synthesized material and alkali activator consisted of strong alkali hydroxide and sodium silicate solution. This review paper elaborated the raw materials, alkali activators, and admixture for geopolymer, and the application of geopolymer-based material for medical purposes. We also discuss the prospective and challenges of geopolymer for the medical field. The adjustable strength and porosity make this material versatile for coating substrates to become bone scaffold material. However, the concern remains about the leaching and high alkalinity of geopolymers. This could be improved by reducing the molarity of sodium hydroxide and mixing geopolymer with compounds to trap the harmful leachate agent inside and studying different solutions for the activation of geopolymer.